Cultural Code In Motion: Animating Indigenous Design Patterns For Contemporary Digital Storytelling - Lestari, Vika Indah; Maharani, Naila Adhiva; Wibowo, Anggi (International Journal of Graphic Design, 2025)
The COVID-19 pandemic has accelerated the integration of digital technologies in education, reshaping how students learn and engage in secondary school settings. This study investigates the influence of digital mindset on student resilience and learning motivation in post-pandemic Indonesian secondary schools. The primary aim is to examine whether students who demonstrate adaptability, openness to change, and confidence in using technology are better equipped to stay motivated and resilient in digitally mediated learning environments. Using a quantitative research design, the study employed a survey method involving 110 secondary school students. Data were collected through structured questionnaires and analyzed using statistical techniques to assess the relationships among the key variables. The findings reveal that digital mindset has a significant and positive impact on both student resilience and learning motivation. Students with stronger digital mindsets are more capable of adapting to challenges, maintaining focus, and demonstrating initiative in their learning processes. They also exhibit greater emotional regulation and perseverance in the face of academic setbacks. This study concludes that developing a digital mindset is essential for fostering student adaptability, engagement, and psychological well-being in contemporary education. The results highlight the importance of integrating digital mindset development into school curricula and teaching practices to build resilient, future-ready learners in an era of rapid technological change.